Vertex Operator Representations of Type $C_l^{(1)}$ and Product-Sum Identities - Hu, Naihong; Xia, Li-Meng (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We construct a class of homogeneous vertex representations of $C_l^{(1)},\; l ≥ 2$, and deduce a series of product-sum identities. These identities have fine interpretation in the number theory.